Methods and Devices for Reducing Air Dust Concentrations - Ahror Tursunov Aminjon o`g`li; Djuraev Sherzod Sobirjonovich (International Journal on Orange Technologies, 2024)
The goals of environmental protection policies are the wise use of natural resources, the avoidance of negative impacts that society's economic activities have on the environment and public health. Ensuring the transition of water to low and closed technological processes in industrial production, as well as developing and introducing waste-free technological processes, cost-effective methods of cleaning industrial and household waste water, air, and solid waste are crucial to reducing environmental pollution.